Pengaruh Harga Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Grab Di Kecamatan Pamulang (Jurnal Manajemen Kreatif dan Inovasi, 2023)
This study aims to determine the effect of price and service quality on Grab customer satisfaction in an area. The population in this study are residents who live in the Pamulang sub-district, Tangerang Selatan city. users of GrabBike and GrabFood services in Pamulang sub-district, Tangerang Selatan city with a sample of 100 respondents. Sampling using purposive sampling technique. Data collection techniques using questionnaires and literature studies as well as by browsing the internet. The data analysis technique used is multiple linear regression. The results show that the price and service quality simultaneously affect Grab's customer satisfaction. Service quality does not partially affect Grab customer satisfaction Prices partially affect Grab customer satisfaction.